PROMOTING TEACHERS’ PROFESSIONAL COMPETENCIES: PROPOSAL OF A FRAMEWORK-SYLLABUS - Cramerotti, Sofia (PUPIL: International Journal of Teaching, Education and Learning, 2020)
The aim of this research is the proposal of a framework-syllabus of teachers’ professional skills and competencies. It involved 207 Italian school teachers. The methodology used was based on different focus groups interspersed by individual moments of self-inquire and self-reflection carry out by the teachers. The methodology included the use of an online survey, too. The survey was used to determine the grade of importance assigned by the participants to the different competencies. The outcome of this study is a framework-syllabus composed of several skills and competencies that characterize the expert teaching profession. The framework-syllabus is structured in 3 macro-areas (professional, teaching and organizing) and 16 competencies expressed in 77 different behavioral indicators. These different competencies delineate four teacher’s profiles of “middle management” in the school’s context. The research also demonstrates the main important and relevant competencies for being an expert teacher.